2018
DOI: 10.4317/medoral.22822
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro study of the accuracy of impression techniques for dental implants: Direct technique with an elastomeric impression material versus intraoral scanner

Abstract: BackgroundThe aim of this study was to compare a conventional technique (elastomeric impression material - EIM) and a digital technique (scanner digital model – SDM) on a six-analog master model (MM) to determine which was the most exact.Material and MethodsTwenty impressions were taken of a master model (EIM) and twenty scanned impressions (SDM) (True Definition). A coordinate measuring machine (CMM) was used to measure the distances between adjacent analogues (1-2, 2-3, 3-4, 4-5, 5-6), intermittently positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 31 publications
5
48
0
6
Order By: Relevance
“…Ultimately, 10 articles representing completely edentulous impressions (9 in vitro studies and 1 clinical study) and 8 articles representing partial edentulous impressions (6 in vitro and 2 clinical studies) met the inclusion criteria and were included in the descriptive analysis. One clinical 12 study and 4 in vitro 21‐24 studies from the completely edentulous and one clinical 11 and one in vitro 25 study from the partially edentulous group were excluded from the meta‐analysis, which included 11 studies overall. Excluded studies 26‐62 and reasons for exclusion are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, 10 articles representing completely edentulous impressions (9 in vitro studies and 1 clinical study) and 8 articles representing partial edentulous impressions (6 in vitro and 2 clinical studies) met the inclusion criteria and were included in the descriptive analysis. One clinical 12 study and 4 in vitro 21‐24 studies from the completely edentulous and one clinical 11 and one in vitro 25 study from the partially edentulous group were excluded from the meta‐analysis, which included 11 studies overall. Excluded studies 26‐62 and reasons for exclusion are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies 12,21‐24,63‐67 evaluated completely edentulous jaws with 2 to 8 implants, while 8 studies 11,13,25,68‐72 investigated situations with a partially edentulous arch with two or more implants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This need for precision is related to the finding that there is a ten-time lower implant mobility compared to the mobility of natural teeth (2). However, all impression methods available today, both conventional and digital, are inevitably prone to errors, which readily explains the high number of studies in this area (4)(5)(6). At closer inspection, nearly all of the investigations addressing this problem are limited to model-based in-vitro setups.…”
Section: Introductionmentioning
confidence: 99%